CAPACITY EVALUATION OF THE BANGLIO CONNECTING CHANNEL AND PUMP STATION USING HEC-RAS HYDRAULIC MODELING - Mohammad Imamuddin; Basit Al Hanif; Andhika Rizky Saputra (University Muhammadiyah Jakarta, 2026)
The Banglio connecting channel (PHB) in Cilincing Subdistrict, North Jakarta, is one of the drainage systems that is frequently affected by flooding during the rainy season and by tidal inundation from the sea. Field observations identified several physical constraints along the channel, including cables crossing the channel, waste accumulation, sedimentation, encroaching structures, and a limited pump operating time caused by the absence of a cooling system. This study aims to evaluate the physical condition and hydraulic capacity of the Banglio channel and pump station in conveying the design flood discharge. Hydrological analysis was carried out using ten years of annual maximum rainfall data from the Tanjung Priok rainfall station, processed through frequency analysis using the Gumbel, Normal, Log Normal, and Log Pearson Type III distributions, followed by a Chi-Square goodness-of-fit test. The design flood hydrograph was generated using the Gamma I Synthetic Unit Hydrograph (SUH) method, while the hydraulic simulation was performed with HEC-RAS software under four scenarios: existing channel without pump, existing channel with pump, planned (normalized) channel without pump, and planned channel with pump. The results show a 10-year design discharge of 13.27 m3/s. The existing channel produced a maximum water level of 4.94 m without the pump and 4.90 m with the pump, both of which exceeded the channel capacity and caused overflow. After normalization, the maximum water level decreased to 1.67 m without the pump and 1.59 m with the pump, and no overflow was observed. These findings indicate that channel normalization combined with pump operation is the most effective alternative for controlling flooding in the study area.Keywords: drainage channel; pump capacity; HEC-RAS; flood discharge; Gamma I synthetic unit hydrograph